Baboon Sociology? Commentary on Daniel Beunza's Taking the Floor - MacKenzie, Donald A (Sociologica (Bologna), 2022)
Beunza's Taking the Floor is a contribution not just to the sociology of finance, but to the social sciences more broadly. Methodologically, the book demonstrates the virtue of returning to a field site using a different research method. Theoretically, it opens up important questions concerning the relationship between mainstream forms of sociological analysis and actor-network theory.